Metagenomic Analysis of Hot Springs in Central India Reveals Hydrocarbon Degrading Thermophiles and Pathways Essential for Survival in Extreme Environments - Saxena, Rituja; Dhakan, Darshan B.; Mittal, Parul; Waiker, Prashant; Chowdhury, Anirban; Ghatak, Arundhuti; Sharma, Vineet K. (Frontiers in Microbiology, 2017)
Extreme ecosystems such as hot springs are of great interest as a source of novel extremophilic species, enzymes, metabolic functions for survival and biotechnological products. India harbors hundreds of hot springs, the majority of which are not yet explored and require comprehensive studies to unravel their unknown and untapped phylogenetic and functional diversity. The aim of this study was to perform a large-scale metagenomic analysis of three major hot springs located in central India namely, Badi Anhoni, Chhoti Anhoni, and Tattapani at two geographically distinct regions (Anhoni and Tattapani), to uncover the resident microbial community and their metabolic traits. Samples were collected from seven distinct sites of the three hot spring locations with temperature ranging from 43.5 to 98°C. The 16S rRNA gene amplicon sequencing of V3 hypervariable region and shotgun metagenome sequencing uncovered a unique taxonomic and metabolic diversity of the resident thermophilic microbial community in these hot springs. Genes associated with hydrocarbon degradation pathways, such as benzoate, xylene, toluene, and benzene were observed to be abundant in the Anhoni hot springs (43.5–55°C), dominated by Pseudomonas stutzeri and Acidovorax sp., suggesting the presence of chemoorganotrophic thermophilic community with the ability to utilize complex hydrocarbons as a source of energy. A high abundance of genes belonging to methane metabolism pathway was observed at Chhoti Anhoni hot spring, where methane is reported to constitute >80% of all the emitted gases, which was marked by the high abundance of Methylococcus capsulatus. The Tattapani hot spring, with a high-temperature range (61.5–98°C), displayed a lower microbial diversity and was primarily dominated by a nitrate-reducing archaeal species Pyrobaculum aerophilum. A higher abundance of cell metabolism pathways essential for the microbial survival in extreme conditions was observed at Tattapani. Taken together, the results of this study reveal a novel consortium of microbes, genes, and pathways associated with the hot spring environment.